Tetramethylpyrazine promotes osteo-angiogenesis during bone fracture repair - Jiangbo Ai; Jingzhou Zheng (Journal of Orthopaedic Surgery and Research)
Abstract Background Nonunion following a long bone fracture has gained a lot of attention due to the dreadful impact on the life quality of tremendous patients. Recent data have demonstrated the important involvement of angiogenesis in improving fracture healing. Tetramethylpyrazine (TMP) is an active component of Chinese herbal medicine with various biological activities including pro-angiogenesis property. However, the activity and mechanism of action of TMP in osteo-angiogenesis during bone fracture repair bone fracture healing remain unknown. In this study, TMP was tested for its specific activities in rat aortic endothelial cells (RAECs) and fractured rat model. Methods The effect of TMP on angiogenesis and migration in RAECs was detected by conducting matrigel tubulogenesis assay and transwell assay. Histopathological changes were observed in the rats from each group using H&E staining. The levels of inflammation and coagulation markers in rats were evaluated by ELISA. The expression of osteogenesis-related genes in rats was assessed by RT-qPCR and western blotting. Results TMP promoted angiogenesis processes and migratory ability in RAECs. TMP improved histopathological changes in fractured rat model. The concentration of inflammatory markers (IL-2, IL-6, IL-1beta) in the serum of fractured rats were suppressed by TMP treatment. TMP also had the potential to inhibit blood coagulation in rat tibia fracture model. In addition, the expression and protein levels of osteogenesis-related markers (ALP, Runx2, and OPN-1) were elevated by TMP in the tissues from the fractured rats. In mechanism, TMP significantly promoted the activation of VEGF/FLK1 pathway in vitro and in vivo. Conclusion TMP accelerated the repair of bone fracture by promoting angiogenesis and osteogenesis.